Переваги використання соціальних мереж для популяризації торгової марки чи продукту - Зубарь, Юлія; Тимовчак-Максимець, Оксана (Видавництво Львівської політехніки, 2014)
In the paper possibilities of promoting a trademark or product on the Internet by means of social networks are considered and advantages of this means of popularization are pointed out.
Keywords: соціальні мережі; популяризація; просування; торгова марка